Benign breast papilloma: Is surgical excision necessary?. Issue 4 (14th October 2019) - Moynihan, Alice; Quinn, Edel M.; Smith, Clare S.; Stokes, Maurice; Kell, Malcolm; Barry, John Mitchel; Walsh, Siun M.
Abstract: In many centers internationally, current standard of care is to excise all papillomas of the breast, despite recently reported low rates of upgrade to malignancy on final excision. The objective of this study was to determine the upgrade rate to malignancy in patients with papilloma without atypia. A retrospective review of a prospectively maintained database of all cases of benign intraductal papilloma in a tertiary referral symptomatic breast unit between July 2008 and July 2018 was performed. Patients with evidence of malignancy or atypia on core biopsy and those with a history of breast cancer or genetic mutations predisposing to breast cancer were excluded. One hundred and seventy‐three cases of benign papilloma diagnosed on core biopsy were identified. Following exclusions, the final cohort comprised of 138 patients. Mean age at presentation was 51. Mean follow‐up time was 9.6 months. The most common symptom was a lump (40%). Of the 124 patients who underwent excision, three had ductal carcinoma in situ and there were no cases of invasive disease, giving an upgrade rate to malignancy of 2.4%. Upgrade to other high‐risk lesions (atypical lobular and ductal hyperplasia and lobular carcinoma in situ) was demonstrated in 15 cases (12.1%). Benign papilloma was confirmed in 100 cases (81.5%), and 6 (4.8%) had no residual papilloma found on final excision. Twelve patients (8.7%) were managed conservatively. Of those, one later went on to develop malignancy. Patients with a diagnosis of benign papilloma without atypia on core biopsy have a low risk of upgrade to malignancy on final pathology, suggesting that observation may be a safe alternative to surgical excision. Further research is warranted to determine which patients can be safely managed conservatively.